IMPLEMENTASI MODERASI BERAGAMA PADA PENDIDIKAN SEKOLAH MINGGU BUDDHA DI VIHARA VAJRA BUMI GIRI PUTRA - Saputro Edi Hartono (Dharmasmrti: Jurnal Ilmu Agama dan Kebudayaan, 2024)
This research aims to describe the implementation of religious moderation in Buddhist Sunday school education at the Vajra Bumi Giri Putra Vihara, so this research focuses on the implementation and understanding of religious moderation carried out by Buddhists at the Vajra Bumi Giri Putra Vihara, especially Buddhist Sunday School students. This research uses a method with a qualitative descriptive approach. This method produces findings obtained through data collected using several means, such as interviews, observations and documentation. Buddhist religious education includes various aspects of Buddhist teachings such as Dhamma (universal law), Sila (morality), and Bhavana (meditation). Buddhist religious education also aims to promote values in accordance with Buddhist teachings such as love, compassion, wisdom, example and peace. Religious education is one of the most effective ways of promoting religious moderation. Through proper and in-depth religious education, individuals can understand religious teachings correctly and practice them in the right way.